Take me on - McGarry, Katie; McGarry, Katie (Don Mills, Ontario, Canada : Harlequin Teen, 2014)
Abandoning kickboxing after a tragedy in the ring, champion fighter Haley is forced to train an attractive mixed martial arts student who secretly fights on Haley's behalf to redeem his troubled past.
Includes bonus novella: Crossing the line.
Keywords: Mixed martial arts -- Fiction; Secrets -- Fiction; Family problems -- Fiction; Love -- Fiction